Glycerol-driven denitratation: process kinetics, microbial ecology, and operational controls. Issue 4 (22nd February 2022) - Baideme, Matthew; Long, Chenghua; Plante, Luke; Starke, Jeffrey; Butkus, Michael; Chandran, Kartik
Abstract : This study implicated stoichiometric limitation of influent organic carbon, unique microbial community enrichment, and differential nitrate and nitrite reduction kinetics as determinant factors in glycerol-driven denitratation. Abstract : Denitratation, the selective reduction of nitrate to nitrite, is a novel process and when coupled with anaerobic ammonium oxidation (anammox) could achieve resource-efficient biological nitrogen removal of ammonium- and nitrate-laden waste streams. Using a fundamentally-based, first principles approach, this study optimized a stoichiometrically-limited, glycerol-driven denitratation process and characterized mechanisms supporting nitrite accumulation with results that aligned with expectations. At the optimal influent chemical oxygen demand to nitrate ratio of 3.0 : 1 identified, glycerol supported selective nitrate reduction to nitrite (nitrite accumulation ratio, NAR = 62%) and near-complete nitrate conversion (nitrate reduction ratio, NRR = 96%), indicating its viability in a denitratation system. Specific rates of nitrate reduction (135.3 mg N per g VSS h −1 ) were at least one order of magnitude greater than specific rates of nitrite reduction (14.9 mg N per g VSS h −1 ), potentially resulting in transient nitrite accumulation and indicating glycerol's superiority over other organic carbon sources in denitratation systems. Optimal stoichiometric limitation pH and ORP inflection points in nitrogen transformation assays corresponded to maximum nitrite accumulation, indicating operational setpoints to prevent further nitrite reduction. Denitratation conditions supported enrichment of Thauera sp. as the dominant genus. Stoichiometric limitation of influent organic carbon, coupled with differential nitrate and nitrite reduction kinetics, optimized operational controls, and a distinctively enriched microbial ecology was identified as causal in glycerol-driven denitratation.